STUDY ON DYNAMIC GAMES - PART OF THE PHYSICAL ACTIVITY MSTUDY ON DYNAMIC GAMES - PART OF THE PHYSICAL ACTIVITY MODERN EDUCATIONAL TOOLODERN EDUCATIONAL TOOL - Andrieș Vasile; Onesim Florin (Editura Univeristatii "Stefan cel Mare" din Suceava, 2021)
The game is one of the most attractive tools with which teachers have the opportunity to achieve their educational goals. The involvement of children in dynamic games makes the activity more attractive and enjoyable, thus increasing the chances that the practice of physical exercises will be a habit both during school activities and in free time. Practiced systematically, the dynamic game can bring benefits to the children, thus being able to form in the students' mentality the automatism to practice them.